(1561) Economic Reform in Egypt-(Motives and Orientations) الإصلاح الاقتصادي في مصر - (الدوافع والتوجهات) - Abd-El-Hai, Mahmoud M. (The Institute of National Planning, 2018)
The economic reform in which Egypt is now involved may be described as a determined action looking for solutions to many accumulated Solon-economic problems.